Today’s Physical Education Teachers: An Inquiry Into Exceptional Practice - Chorney, David W. (Alberta Journal of Educational Research, 2010)
The purpose of this article is to provide an overview of the findings from a study of the professional lives of four physical education specialist teachers considered exceptional and to explain why they engage in their practice as they do. The issues of how teachers develop as well as how they change during their careers is emphasized. The conclusion highlights some of the most important qualities of exemplary teachers of physical education and opens the discussion for all professional educators, not only those in physical education, but at all levels and curricular backgrounds to search within themselves to determine how they teach and how they have changed over time.